2016
DOI: 10.1097/bot.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Mobility and the Change in Activities of Daily Living After Hip Fracture

Abstract: Prognostic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
77
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 34 publications
11
77
1
7
Order By: Relevance
“…Two other studies (Mariconda et al and Gonzalez Zabaleta et al ) investigated predictors for IADL after a hip fracture. Older age, higher ASA classification and lower prefracture IADL were found to be predictors in these studies, which is in accordance with the present results . Furthermore, Mariconda et al found that prefracture ambulatory ability and postoperative complications were associated with IADL, as we did.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two other studies (Mariconda et al and Gonzalez Zabaleta et al ) investigated predictors for IADL after a hip fracture. Older age, higher ASA classification and lower prefracture IADL were found to be predictors in these studies, which is in accordance with the present results . Furthermore, Mariconda et al found that prefracture ambulatory ability and postoperative complications were associated with IADL, as we did.…”
Section: Discussionsupporting
confidence: 93%
“…Age, ASA classification, prefracture living situation and use of walking aids were predictors for baseline IADL. Sex, prefracture living with a partner and type of fracture were not predictors for lower baseline IADL in the present multivariate analysis, in accordance with other cohort studies . Two previous studies showed that an extracapsular fracture is more common in older patients with more comorbidities and lower functional recovery .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Approximately half of hip fracture patients who survive to 1 year do not regain their prior functionality (25) nor does their health status return to prefracture levels. (30) Of patients surviving 1 year who needed no walking aids prior, approximately 40% require assistance. (30) Of patients surviving 1 year who needed no walking aids prior, approximately 40% require assistance.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
“…(26) Only about one-third to one-half of hip fracture survivors regain prior ambulatory function, (27)(28)(29) and around 13% may be unable to ambulate at all. (30) Loss of autonomy and independence is also reflected in changes of residential settings after fracture. (30) Loss of autonomy and independence is also reflected in changes of residential settings after fracture.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%